Unemployment, poverty and arrests in the Georgia black belt - Arthur, John A. (American journal of criminal justice, 1991)
Although Blacks have made economic progress since 1960, these gains have been overshadowed by soaring crime rates. The purpose of this paper is to examine the effects of unemployment and economic deprivation on Black arrests using data from 50 predominantly rural counties in Georgia where Blacks comprise 40 percent of the population. The study concludes that Black arrests in the 50 counties forming Georgia’s Black Belt may be linked to the economic and structural conditions associated with Black unemployment, economic deprivation, and the occupational segregation of Blacks to secondary, low-paying jobs. The findings lend plausibility to the notion that the low socioeconomic status of Blacks, coupled with their lack of access to the macrostructural opportunity system creates conditions favoring normative violations. The findings therefore furnish tentative support for opportunity-structure theory of crime that asserts that the lack of access to opportunity plays a salient role in understanding the causal nexus of Black involvement in crime.